2010
DOI: 10.1021/np100517u
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Triterpenoids from Maytenus retusa

Abstract: Seven new triterpenoids (1-7) and 36 known compounds were isolated from the root bark of Maytenus retusa. Their structures were determined by 1D and 2D spectroscopic studies. Several compounds were evaluated for their cytotoxicity against the human tumor cell lines HL-60 and MCF-7. Some of them were cytotoxic, with IC(50) values ranging between 0.2 and 4.7 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…They include potent antitumor maytansinoids, macrocyclic spermidines, amphetaminelike sympathomimetic (−)-S-cathinone, terpenoids, cytotoxic cardenolides, and flavonoids [1][2][3]. The Celastraceae family is also a rich source of several terpenoids such as friedelane type-triterpenes (quinonemethide, enequinone-methide, and phenolic types), lupanes, oleananes, several types of dimeric triterpenes, diterpenes such as kaurane and abietane, sesquiterpenes, and sesquiterpene-triterpene hetero-Diels-Alder adducts [4][5][6][7][8]. However, the most widespread and characteristic metabolites of this family are a large group of unusually highly oxygenated sesquiterpenoids, based on the 5,11-epoxy-5β,10αeudesman-4-(14)-ene skeleton known as dihydro-β-agarofurans.…”
mentioning
confidence: 99%
“…They include potent antitumor maytansinoids, macrocyclic spermidines, amphetaminelike sympathomimetic (−)-S-cathinone, terpenoids, cytotoxic cardenolides, and flavonoids [1][2][3]. The Celastraceae family is also a rich source of several terpenoids such as friedelane type-triterpenes (quinonemethide, enequinone-methide, and phenolic types), lupanes, oleananes, several types of dimeric triterpenes, diterpenes such as kaurane and abietane, sesquiterpenes, and sesquiterpene-triterpene hetero-Diels-Alder adducts [4][5][6][7][8]. However, the most widespread and characteristic metabolites of this family are a large group of unusually highly oxygenated sesquiterpenoids, based on the 5,11-epoxy-5β,10αeudesman-4-(14)-ene skeleton known as dihydro-β-agarofurans.…”
mentioning
confidence: 99%
“…The antimicrobial activity of the isolated compounds from P. campestris confirmed the results obtained with STAMP method. P. campestris was chosen for the MIC experiment because it contains substances named quinonemethide triterpenoids, such as maytenin and netzahualcoyone, that are chemotaxonomic markers of the Celastraceae family, and that exhibit a myriad of biological activities [15,16]. The results we obtained with the powdered plant material of P. campestris using the STAMP method and the results of maytenin and netzahualcoyone using the MIC method were similar and showed greatest antimicrobial activity against S. aureus, followed by C. parapsilosis and C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…Pristimerin ( 26 ) was toxic to PBMC (peripheral blood mononuclear cells) in the same concentration range, suggesting that this compound is relatively unselective [19]. Another assay showed the cytotoxic potential of pristimerin ( 26 ) against HL-60 (IC 50 = 0.2 µM) and MCF7 (breast adenocarcinoma) (IC 50 = 0.4 µM) cell lines [77]. Recently, the NCI-60 cell line screen revealed that pristimerin ( 26 ) was active against UO-31 (renal carcinoma), T-47D (breast cancer), and A549 (non-small-cell lung cancer) human tumor cell lines with individual half maximal inhibition of cell proliferation (GI 50 ) values ranging from 0.12 µM to 1.2 µM [78]; therefore, pristimerin ( 26 ) would deserve further in vivo evaluation.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%